Cephalopod genomics: A plan of strategies and organization. Issue 1 (July 2012) - Albertin, Caroline; Bonnaud, Laure; Brown, C.; Crookes-Goodson, Wendy; Fonseca, Rute; Cristo, Carlo; Dilkes, Brian; Edsinger-Gonzales, Eric; Freeman, Robert; Hanlon, Roger; Koenig, Kristen; Lindgren, Annie; et al.
Abstract The Cephalopod Sequencing Consortium (CephSeq Consortium) was established at a NESCent Catalysis Group Meeting, "Paths to Cephalopod Genomics-Strategies, Choices, Organization, " held in Durham, North Carolina, USA on May 24–27, 2012. Twenty-eight participants representing nine countries (Austria, Australia, China, Denmark, France, Italy, Japan, Spain and the USA) met to address the pressing need for genome sequencing of cephalopod mollusks. This group, drawn from cephalopod biologists, neuroscientists, developmental and evolutionary biologists, materials scientists, bioinformaticians and researchers active in sequencing, assembling and annotating genomes, agreed on a set of cephalopod species of particular importance for initial sequencing and developed strategies and an organization (CephSeq Consortium) to promote this sequencing. The conclusions and recommendations of this meeting are described in this white paper.